Performance of colocasia in hot arid region of western Rajasthan (Indian Journal of Arid Horticulture, 2020)
The present study was conducted to evaluate the performance of colocasia under full shade, partial shade and open conditions of hot arid region of western Rajasthan. Result revealed that the vegetative growth characteristics i.e. plant height (31.20 cm), numbers of leaves/plant (2.70), leave length (21.60 cm) and leave width (20.20 cm) and yield attributes and quality attributes like dry matter percentage were recorded highest when colocasia was grown under aonla plantation (8 x 8 m) followed by colocasia grown under 100% shade condition and lower yield was observed under open conditions. Maximum numbers of cormels/plant (5.60), corm length (6.20 cm), corm diameter (9.20 cm), average corm weight (32.00 g), cormel length (4.30 mm), cormel diameter (8.10 mm) and cormel weight (18.90 g) were recorded when colocasia was grown in aonla plantation followed by colocasia grown under fully shade condition and lower values for yield attributes of colocasia was recorded under open field condition in the arid region.
Keywords: Colocasia esculenta L; open condition; shade condition; yield attributes